HUBUNGAN ANTARA KUALITAS TIDUR DENGAN TEKANAN DARAH PADA LANSIA DI PANINGGILAN UTARA, CILEDUG - Siti Khadijah, (2022)
Background: Sleep is a need that must be fulfilled. Sleep is essential for each individual and it can be grouped according to age, both in terms of quantity and quality of sleep. Sleep quality is a condition where a person rests his body and when he wakes up he can be more fit, comfortable and his body condition improves. If sleep is disturbed then blood pressure is also disturbed so that it can cause an increase in blood pressure. Purpose: writing a scientific paper is to find out the relationship between sleep quality and blood pressure in the elderly in Paninggilan Utara, Ciledug. Methods: This research is a correlational study with a cross-sectional study approach with a total sample of 67 respondents. Measuring Instruments: Collecting data for sleep quality using the Pittsburgh Sleep Quality Index (PSQI) questionnaire and for blood pressure using a spynomanometer. Data Results: This study used SPSS 25 with a correlation test using Spearman's rho with p=0.048 (<0.05). Conclusion: There is a relationship between sleep quality and blood pressure in the elderly in North Paninggilan, Ciledug with a correlation coefficient of 0.242 with a weak and unidirectional relationship.